Patterns of surgical care for women with ovarian cancer in New South Wales. (26th May 2020) - White, Kahren M.; Walton, Richard J.; Zhao, George W.; Creighton, Nicola; Farrell, Rhonda; Saidi, Samir; Herbst, Unine; Hogg, Russell; Currow, David C.
Abstract : Background: Little is known about the delivery of surgical services and outcomes for women with ovarian cancer across New South Wales (NSW). Aim: The study objective was to provide a descriptive analysis of the proportion of women who had surgery for ovarian cancer in NSW in specialist gynaecological oncology hospitals and compare outcomes for women attending specialist and non‐specialist services in NSW. Materials and Methods: This study is a retrospective analysis of women with primary ovarian, fallopian tube or peritoneal cancer from 2009 to 2012. Data were analysed from the NSW Cancer Registry, NSW Admitted Patient Data Collection and Register of Births Deaths and Marriages. Treating hospitals were characterised as public specialist, public non‐specialist and private. Morbidity and mortality outcomes are reported. Results: The study included 1106 women. Fifty‐seven hospitals performed surgery: seven public specialist, 27 private and 23 public non‐specialist hospitals. The highest proportion of surgery was performed in public specialist hospitals (61%). There was considerable variation in the utilisation of public specialist hospitals between local health districts. There was no significant difference in outcomes related to the type of hospital where surgery was performed. Conclusions: Although the majority of women are having surgery in a specialist gynaecological oncology public hospital across NSW, many are not. Women living in regional and remote NSW were less likely to have their surgery in a specialist hospital. This is the first step in understanding where women in NSW are currently receiving their surgical care, as well as the outcomes related to this.